Geriatric presentation to the emergency department-spectrum of illness and co-relation with social factors - Hanumanthaiah, Ramesh Gorghatta; Farhath, Sheerin; Prasanna Bangalore Krishnappa, Panchakshari; P., Dheemantha; Ranganath, T. S. (International Journal of Advances in Medicine, 2018)
Background: Increase in the elderly population presenting to Emergency Department is a prime concern as it has maximum implications on the delivery of health care. Older patients account for 12%-24% of all ED patients worldwide. A need for this study is to understand and analyze the current and future of Emergency department (ED) and examines the presentation of geriatric patient to emergency department in our institute in an urban setup of the fastest growing population segment in the city. Methods: An observational study over a period of one year from 2015 to 2016. All patients aged 60 years and above, visiting the Emergency Medicine. The following data were obtained. (I) Demographics, (II) Urban and Rural population (III) Presence of co-morbidities, (IV) Common conditions (V) Clinical symptoms and Diagnoses, Socio-demographic data collected directly from patient or immediate caregiver. Results: Total No of patients included during the study were 5489. Data was assessed male patient, predominance was found with 61%, 39% female. The urban population 74.8% was more predominant. Rural being at 25.2%, 1620 (29.2%) poisoning cases,1322 (24.1%) trauma cases,318 (5.8%) cancer cases, 247(4.5%) COPD cases and 230 (4.2%) stroke cases were encountered. Male72.58%, females 27.42%. CCU 58.5% male, 41.55% females. ICU 55.21% males and 44.79 % females. The average time was 3.75 to 4.25. Conclusions: Road Traffic accidents and poisoning together contributed to many cases. Observation was inadequate training amongst ED doctors and nurses in assessing and managing Trauma patients who lack ATLS protocols in stabilizing geriatric emergencies. Hence ED staff should be well trained to facilitate management of an ageing patients. Hazmat bay should be well organized with specific antidotes to the commonly available poisons. Atypically presentation was common in ED. Considerable overlapping of symptoms were commonly encountered in patients presenting to Emergency department.